Per-length biomass estimates of Antarctic krill (Euphausia superba) - Abigail J. R. Smith; Simon J. Wotherspoon; Martin J. Cox; Martin J. Cox (Frontiers in Marine Science, 2023)
Total biomass and areal biomass density are often necessary to establish ecological relationships and enable informed management decisions, in particular setting fisheries catch limits. Further refining these estimates to sub-population biomass based on length informs ecological models of predator-prey dynamics, ecosystem energy transfer and biogeochemical cycles; however, measures of uncertainty in these per-length biomass estimates are needed. We present a statistical method to calculate the per-length biomass of Antarctic krill (Euphausia superba) from conversion factors using acoustic and net sample data. Variability in krill length-frequency, and wetmass introduced by net sampling is also explored through non-parametric bootstrapping. We applied this method on a 1 mm length window to active acoustic and net sample data collected during an Antarctic krill biomass survey in CCAMLR Division 58.4.2 (62 – 67°S; 55 – 80°E, with a survey area of 775,732 km2) performed between February – March 2021. We found that 77% of the total estimated biomass was attributable to krill of length 14 – 49 mm. The largest biomass of krill in a single length bin was estimated as 340,000 t (95% CI: 148,000 - 408,000 t) and was found in the 49 mm length bin (i.e., 48.5 to 49.5 mm). This method will allow future surveys (with sufficient data) to estimate biomass of krill on a per-length basis along with associated uncertainty (confidence intervals) derived from net sampling and so may be used to provision size-based ecosystem models with krill biomass.